Steroidogenic Activity of StAR Requires Contact with Mitochondrial VDAC1 and Phosphate Carrier Protein - Bose, Mahuya (American Society for Biochemistry and Molecular Biology, 2008)
The steroidogenic acute regulatory protein (StAR) is required for adrenal and gonadal steroidogenesis and for male sexual differentiation. StAR acts on the outer mitochondrial membrane (OMM) to facilitate movement of cholesterol from the OMM to the inner mitochondrial membrane to be converted to pregnenolone, the precursor of all steroid hormones. The mechanisms of the action of StAR remain unclear; the peripheral benzodiazepine receptor, an OMM protein, appears to be involved, but the identity of OMM proteins that interact with StAR remain unknown. Here we demonstrate that phosphorylated StAR interacts with voltage-dependent anion channel 1 (VDAC1) on the OMM, which then facilitates processing of the 37-kDa phospho-StAR to the 32-kDa intermediate. In the absence of VDAC1, phospho-StAR is degraded by cysteine proteases prior to mitochondrial import. Phosphorylation of StAR by protein kinase A requires phosphate carrier protein on the OMM, which appears to interact with StAR before it interacts with VDAC1. VDAC1 and phosphate carrier protein are the first OMM proteins shown to contact StAR.